Development and Standardization of a Furosemide Stress Test to Predict the Severity of Acute Kidney Injury - Chawla, Lakhmir S; Davison, Danielle L; Brasha-Mitchell, Ermira; Koyner, Jay L; Arthur, John M; Shaw, Andrew D; Tumlin, James A; Trevino, Sharon A; Kimmel, Paul L; Seneff, Michael G (Critical care (London, England), 2013)
In the setting of early acute kidney injury (AKI), no test has been shown to definitively predict the progression to more severe stages. We investigated the ability of a furosemide stress test (FST) (one-time dose of 1.0 or 1.5 mg/kg depending on prior furosemide-exposure) to predict the development of AKIN Stage-III in 2 cohorts of critically ill subjects with early AKI. Cohort 1 was a retrospective cohort who received a FST in the setting of AKI in critically ill patients as part of Southern AKI Network. Cohort 2 was a prospective multicenter group of critically ill patients who received their FST in the setting of early AKI. We studied 77 subjects; 23 from cohort 1 and 54 from cohort 2; 25 (32.4%) met the primary endpoint of progression to AKIN-III. Subjects with progressive AKI had significantly lower urine output following FST in each of the first 6 hours (p<0.001). The area under the receiver operator characteristic curves for the total urine output over the first 2 hours following FST to predict progression to AKIN-III was 0.87 (p = 0.001). The ideal-cutoff for predicting AKI progression during the first 2 hours following FST was a urine volume of less than 200mls(100ml/hr) with a sensitivity of 87.1% and specificity 84.1%. The FST in subjects with early AKI serves as a novel assessment of tubular function with robust predictive capacity to identify those patients with severe and progressive AKI. Future studies to validate these findings are warranted.